2001
DOI: 10.1055/s-0037-1612918
|View full text |Cite
|
Sign up to set email alerts
|

Platelets Exposed to Elevated Levels of Endogenous Thrombopoietin In Vivo Have a Reduced Response to Megakaryocyte Growth and Development Factor In Vitro

Abstract: SummaryThrombopoietin (TPO), or megakaryocyte growth and development factor (MGDF), has been shown to potentiate the sensitivity of normal human platelets to various agonists in vitro. The present study investigated the functional and biochemical properties of platelets from mice rendered thrombocytopenic by sublethal irradiation with regard to the reactivity to recombinant murine MGDF (rmMGDF) in vitro. During the course of reversible thrombocytopenia following irradiation, platelets from irradiated mice whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 47 publications
3
9
0
Order By: Relevance
“…In addition, rhTPO is able to phosphorylate c-Mpl only in platelets from SA patients and healthy control subjects but not in those from UA patients, further supporting this hypothesis. Platelets from patients with UA also showed reduced reactivity to rhTPO ex vivo, possibly related to their exposure in vivo to increased levels of endogenous TPO, analogously to what was previously shown for thrombocytopenic mice (33) and humans with the syndrome of congenital thrombocytopenia with absent radii (33,34).…”
Section: Discussionsupporting
confidence: 73%
“…In addition, rhTPO is able to phosphorylate c-Mpl only in platelets from SA patients and healthy control subjects but not in those from UA patients, further supporting this hypothesis. Platelets from patients with UA also showed reduced reactivity to rhTPO ex vivo, possibly related to their exposure in vivo to increased levels of endogenous TPO, analogously to what was previously shown for thrombocytopenic mice (33) and humans with the syndrome of congenital thrombocytopenia with absent radii (33,34).…”
Section: Discussionsupporting
confidence: 73%
“…Such decreased prothrombotic effects of PEG‐rHuMGDF in thrombocytopenic rats might be related not only to a low platelet number but also to decreased platelet reactivity to PEG‐rHuMGDF in the thrombocytopenic state. The latter possibility was based on our previous findings that platelets from thrombocytopenic mice had decreased surface levels of c‐Mpl and decreased reactivity to TPO in a platelet aggregation response in vitro , possibly because of increased endogenous TPO concentration [12]. Consistent with these observations, this study confirmed that serum TPO concentrations were elevated in thrombocytopenic rats (Fig.…”
Section: Effects Of Peg‐rhumgdf In Thrombocytopenic Ratssupporting
confidence: 87%
“…We used the mouse TPO ELISA [12] to measure TPO concentrations in rat plasma with some modifications. Nunc‐Immuno plates (Nunc, Roskilde, Denmark) were incubated with 5 μg mL −1 rabbit immunoglobulin G antibody against recombinant mouse TPO at 4 °C overnight and washed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum thrombopoietin (TPO) concentrations were measured using sandwich enzyme-linked immunosorbent assay (ELISA) as previously described (22). A double-staining technique and flow cytometry were used to measure megakaryocyte ploidy (35).…”
Section: Methodsmentioning
confidence: 99%